EVALUASI KEPUASAN ANGGOTA PD IAI KALIMANTAN SELATAN TERHADAP PENGGUNAAN APLIKASI SIAP MENGGUNAKAN METODE EUCS (END USER COMPUTING SATISFACTION) - Surya Wahyudi; Herningtyas Nautika Lingga; Muhammad Ikhwan Rizki (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2022)
The Indonesian Pharmacists Association or Ikatan Apoteker Indonesia (IAI) is a professional organization of pharmacists in Indonesia. IAI has management at Central, Regional, and Branches. Organizational services for each IAI member use the Pharmacist Information System Application or Sistem Informasi Apoteker (SIAp). Evaluation of satisfaction in the Information System can use the EUCS (End User Computing Satisfaction) method. The purpose of this study was to determine the level of satisfaction of South Kalimantan pharmacists on the use of the SIAp application and management services. The research method uses an analytical survey with a cross sectional design. The instrument used is a questionnaire that has been tested for validity and reliability. This research has been submitted to the Research Ethics Commission. The population of this research is 1.151 pharmacists in South Kalimantan. Respondents who filled out the questionnaire were 540 pharmacists (95% confidence level). Questionnaires were distributed using a Google form that assessed the SIAP application from the aspects of Content, Accuracy, Format, Easy of User, and Timeliness. The results of the questionnaire were analyzed using a Likert scale, then the percentage of satisfaction levels interpreted with the categories very high (75.01 - 100%), high (58.34-75), less (41.65-58.33), low (24.98 -41.66), and very low (0-24.99). The results showed that members' satisfaction with the SIAp application from the aspect of Content 79.83% (very high), Accuracy 81.47% (very high), Format 82.32% (very high), Easy of Use 78.36% (very high), and Timeliness 75.52% (very high). Member satisfaction with Branches is 79.07% (very high), Regional is 77.93% (very high), and Central is 75.27% (very high). Conclusion: The level of satisfaction of PD IAI South Kalimantan Pharmacists with the SIAp Application is very high. Branch, Regional, and Central Services are very high.